2001
DOI: 10.12968/bjon.2001.10.5.5360
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two coated catheters in intermittent self-catheterization

Abstract: Intermittent self-catheterization (ISC) has addressed the problems of mechanical or functional urological voiding since the 1970s. Patient quality of life is enhanced by the increased independence and security offered by ISC (Lapides et al, 1972). A randomized, comparative crossover study was undertaken in two centres to evaluate the performance of SpeediCath (Coloplast) and Lofric (Astra Tech) catheters. A total of 27 subjects were recruited, all of whom had been performing ISC more than twice a day for longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Spinu 2012 (NRS) (38) Vapnek 2003 (RCT) (24) De Ridder 2005 (RCT) (25) Pachler 1999 (RCT) (17) Cardenas and Hoffman 2009 (RCT) (36) Bennett 1997 (RCT) (16) Cardenas 2011 (RCT) (30) Fingerhut 1997 (RCT) (14) Charbonneau-Smith 1993 (NRS) (39) Moore 2006 (RCT) (26) Quigley PA 1993 (RCT) (12) Duffy LM 1995 (RCT) (13) Sùrensen 1999 (RCT) (18) Mauroy 2001 (RCT) (20) BIERING-SØRENSEN 2007 (RCT) (29) Costa 2013 (RCT) (33) Chartier-Kastler 2013 (RCT) (34) Chartier-Kastler 2011 (RCT) (31) Domurath 2011 (RCT) (32) Johansen 2007(NRS) (40) Johansson 2013 (RCT) (35) Denys 2012 (NRS) (41) Diokno 1995 (NRS) (42) Fader 2001 (RCT) (21) Pascoe 2001 (RCT) (22) Witjes 2009 (RCT) (37) Wyndaele 2000 (RCT) (19) Ginnantoni 2001 (RCT) (23) Waller 1997 (RCT) (15) PEARMAN 1991(RCT) (11) Sekiguchi et al 2007 (RCT) (28) 0% 20% 40% 60% 80% 100%…”
Section: Other Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Spinu 2012 (NRS) (38) Vapnek 2003 (RCT) (24) De Ridder 2005 (RCT) (25) Pachler 1999 (RCT) (17) Cardenas and Hoffman 2009 (RCT) (36) Bennett 1997 (RCT) (16) Cardenas 2011 (RCT) (30) Fingerhut 1997 (RCT) (14) Charbonneau-Smith 1993 (NRS) (39) Moore 2006 (RCT) (26) Quigley PA 1993 (RCT) (12) Duffy LM 1995 (RCT) (13) Sùrensen 1999 (RCT) (18) Mauroy 2001 (RCT) (20) BIERING-SØRENSEN 2007 (RCT) (29) Costa 2013 (RCT) (33) Chartier-Kastler 2013 (RCT) (34) Chartier-Kastler 2011 (RCT) (31) Domurath 2011 (RCT) (32) Johansen 2007(NRS) (40) Johansson 2013 (RCT) (35) Denys 2012 (NRS) (41) Diokno 1995 (NRS) (42) Fader 2001 (RCT) (21) Pascoe 2001 (RCT) (22) Witjes 2009 (RCT) (37) Wyndaele 2000 (RCT) (19) Ginnantoni 2001 (RCT) (23) Waller 1997 (RCT) (15) PEARMAN 1991(RCT) (11) Sekiguchi et al 2007 (RCT) (28) 0% 20% 40% 60% 80% 100%…”
Section: Other Biasmentioning
confidence: 99%
“…Four articles directly compared different hydrophilic catheters (Aquacath, Easycath, Flocath, Lofric, Silky, Speedycath) in terms of satisfaction and preference reported by the patients (Table 3c). [20][21][22]37 Fader et al 21 reported a significant higher satisfaction rate in patients using Easycath or Lofric, when compared with Aquacath or Silky. Similarly, Pascoe et al 22 demonstrated a statistical difference.…”
Section: Patient's Satisfaction and Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…This was based on userfriendliness 56 and convenience, discretion and speed of use. 57 They also expressed a wish to switch from PVC to Lofric. 58 Other studies have included patients with neurogenic bladder in mixed populations, 28,30,59,60 but as the data are not separately reported for the neurogenic patients, interpretation is difficult.…”
Section: Quality Of Life and Satisfaction With Hydrophilic Catheters mentioning
confidence: 99%
“…Other heterogeneous neurogenic bladder populations including small numbers of patients with spina bifida and multiple sclerosis preferred SpeediCath over Lofric. This was based on user‐friendliness56 and convenience, discretion and speed of use 57. They also expressed a wish to switch from PVC to Lofric 58.…”
Section: Quality Of Life and Satisfaction With Hydrophilic Catheters mentioning
confidence: 99%